Needs Analysis of Cognitive Conflict Teaching Materials Integrated with Augmented Reality Alternative Energy Material - Metia Husra Husnuzan; Fatni Mufit (Physics Learning and Education, 2023)
The development of cognitive conflict-based learning models can improve understanding of physics concepts and remediate students' misconceptions. Teaching materials are usually arranged in a complete and systematic manner based on the learning principles used by teachers and students in the learning process. Teaching materials are very systematic because they are arranged sequentially making it easier for students to use them. This study aims to determine the need for cognitive conflict teaching materials that are integrated with Augmented Reality (AR) so as to increase high school students' conceptual understanding of alternative energy materials. This type of research is preliminary research. The instrument used was a questionnaire to analyze the needs of learning devices and the implementation of physics learning as well as analysis of journals to analyze students' conceptual understanding of alternative energy materials. This test was administered to 122 students from two different schools, and to 2 physics teachers at different schools. Data were analyzed quantitatively and qualitatively. The results of the study state that learning in schools is still focused on teachers and teaching materials have not been integrated with Augmented Reality (AR). The results of the analysis of students' conceptual understanding journals on alternative energy material are still low and misconceptions occur. Therefore, from the results of preliminary research it is necessary to develop cognitive conflict-based physics teaching materials that are integrated with augmented reality technology according to the demands of 21st century learning.P